2021
DOI: 10.1007/s40279-020-01412-7
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Differences in Running Injuries: A Systematic Review with Meta-Analysis and Meta-Regression

Abstract: Background Running is a popular sport with high injury rates. Although risk factors have intensively been investigated, synthesized knowledge about the differences in injury rates of female and male runners is scarce. Objective To systematically investigate the differences in injury rates and characteristics between female and male runners. Methods Database searches (PubMed, Web of Science, PEDro, SPORTDiscus) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 103 publications
(116 reference statements)
4
19
1
1
Order By: Relevance
“…Another key message that should be noted was the variances explained in the PC2 in females (33.76%) and males (12.74%) in the LR region, which suggested that female runners had higher variations of LR as speeding up. This was consistent with findings reported from a recent review that female runners had a higher risk of bone stress injuries than male runners, which related to LRs from landing impact (Hollander et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Another key message that should be noted was the variances explained in the PC2 in females (33.76%) and males (12.74%) in the LR region, which suggested that female runners had higher variations of LR as speeding up. This was consistent with findings reported from a recent review that female runners had a higher risk of bone stress injuries than male runners, which related to LRs from landing impact (Hollander et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…There were no differences in sex, age, BMI or competition distance between athletes that reported an injury/illness and those who did not. Regarding the comparison by sex, a recent systematic review found no differences between the overall injury rate between females and males [20.8 per 100 (95% CI 19.9-21.7) vs. (20.4 (95% CI 19.7-21.1) respectively] [27]. Observing competition distance, a higher incidence of injury in females competing in 10 kilometres or less (RR of 1.08; 95% CI: 1.04-1.39) was the only finding, but the analysis did not incorporate trail running studies [27].…”
Section: Discussionmentioning
confidence: 99%
“…This may help to evaluate the impact of MSKI on race performance and withdrawal, as MSKI can lead to performance decrement (Fallon, 1996) and race withdrawal in 0.7%-4.8% of runners (Hutson, 1984;McGowan and Hoffman, 2015). Further, most studies include both sexes and sex difference have not been examined separately, however, it may be of interest as in non-UER females have more bone stress injuries while male runners more Achilles tendon injuries, although overall injury rates in non-UER athletes are similar (20.8 injuries/1000 females and 20.4 injuries/1000 males) (Hollander et al, 2021). Generally, there is less research in female UER, and it would be important to examine sex differences, as key aspects of female athlete physiology warrant careful consideration, e.g., RED-S that may lead to physiological impairments resulting in an increased risk of bone stress injuries (Tiller et al, 2021).…”
Section: Future Research Directionsmentioning
confidence: 99%